Family Coping Can Improve Interpersonal Nursing Interaction in Implementing Family Nursing with Hypertension - kholifah, siti nur; wibrata, dwi ananto; minarti, minarti minarti; suprajitno, Suprajitno suprajitno (International Journal of Public Health Science (IJPHS), 2020)
Family an important role for hypertension clients providing them with supports, care, and collaborates with nursing for home visit purposes. In fact, not all families have a adequate response when nurses carry out family nursing care. The purpose of this study is to analyze relationship between family coping and the nurse interpersonal interaction when delivering family nursing care for client with hypertension. This study use an observational analytic method. The samples are the nurses working at the Puskesmas of Surabaya District Health Office.The study uses multistage sampling, recruited 110 nurses in total. Variables include family coping and interpersonal interactions. It uses questionnaire for collecting information and the validity and reliability of the questionnaires have been tested. The result of statistical analysis of spearman rho showed that family coping can improve interpersonal nursing interaction (r score 0.382). Family is responsible for providing various facilities for client with hypertension. Families may acts as care givers and establishing good relationships with nurses and other health teams is crucial. Effective coping supports the success of family nursing care for client with hypertension. The Families are encouraged to maintain effective coping while maintained good communication and accepted hypertension clients in the family.